Psychotherapy with somatosensory stimulation as a complementary treatment for women with endometriosis-associated pain – a qualitative study - Anna Limmer; Annemarie Weber; Elisabeth Olliges; Jana Kraft; Florian Beissner; Christine Preibisch; Karin Meissner (BMC Complementary Medicine and Therapies)
Abstract Objective This qualitative study aimed to explore patients’ experiences with a novel treatment approach for endometriosis-associated pain, termed ‘sinosomatics’. Specifically, it sought to understand women’s experiences of the treatment and its components, the effects of the treatment on biological, psychological, and social levels, and how the women interpreted the changes they experienced. Methods We conducted ten semi-structured interviews with patients, who had undergone the complementary treatment for endometriosis-associated pain. These interview sessions were audio-recorded, transcribed, and analyzed using Mayring’s content analysis method with the aid of MAXQDA software. Results Three key categories emerged: ‘treatment experience,’ ‘treatment effects,’ and ‘explanation for effects’. The treatment was described as a “turning point” in patients’ lives, offering new insights into the involvement of psychosocial factors in endometriosis-associated pain and paving the way for overcoming adverse life events. The therapy strengthened women’s empowerment, inspired hope, fostered coping strategies, and promoted personal growth. Both the holistic view of body and mind and the psychological approach to treatment led to a change in the way how women perceived the disease. Conclusions Patients recognized the innovative combination of psychotherapy and acupuncture point stimulation as a significant advancement in managing their disease. The treatment has helped them to acquire a more holistic understanding of their bodily complaints and to cope more effectively with their symptoms. The findings highlight the importance of a patient-centered and empathetic treatment approach that empowers women to take an active role in managing their condition.